Reaching End Users (REU) Socioeconomic Endline Survey 2009, Mozambique - International Food Policy Research Institute; International Potato Center (International Food Policy Research Institute, 2015)
Between 2006 and 2009, HarvestPlus conducted the Reaching End Users (REU) project in Mozambique and Uganda. The objective of the project was to distribute the first biofortified crop with high micronutrient density, provitamin A-rich orange-fleshed sweet potato (OFSP). HarvestPlus selected regions of Uganda and Mozambique for this initiative because in these areas of each country white- or yellow-fleshed sweet potato is either the staple crop (Uganda) or an important secondary source of starch (Mozambique). The project strategy involved conducting a coordinated three-pronged approach to encourage adoption and consumption of OFSP including: (i) vine distribution and agricultural extension (seed systems), (ii) demand creation through nutrition trainings; and (iii) trainings in marketing and product development. HarvestPlus planned to reach over 10,000 farming household in each country, but also wanted to use this opportunity to learn about how the impact and cost-effectiveness of integrated dissemination strategies of differing intensity. The data were used for a rigorous impact evaluation and cost-effectiveness study of the REU OFSP project conducted from 2006-2009 in Mozambique, and the 2012 data were collected to understand how adoption and dietary intakes had evolved. HarvestPlus collaborated with the International Food Policy Research Institute (IFPRI) and the International Potato Center (CIP) to design and implement a randomized-controlled evaluation during the implementation of the REU project in each country. The point of intervention for the REU project included local farmer groups in Uganda and more loosely organized community or church-based groups in Mozambique. Before the intervention, these groups were sampled for the evaluation study and group members with young children were randomly selected for the evaluation household sample. Baseline surveys were conducted in the sampled church groups in Mozambique in 2006. The baseline included a detailed socioeconomic and agricultural survey as well as a nutrition and dietary intake survey. The dietary intake survey included 24-hour dietary recall interviews to measure intakes of vitamin A and other nutrients of target groups of young children and women in the sample. As a basis for identifying impact through the evaluation, sampled farmer groups or church groups were randomly assigned into one of three intervention arms: the intensive 2-3 year intervention (Model 1), a less intensive intervention with reduced activity after the first year (Model 2) and a Control group. In 2009, endline surveys were conducted in Mozambique, and in 2012, the communities were visited a third time, three years after the intervention had left.